IMPACT OF AGGRESSIVE ENVIRONMENT ON TECHNIQUES USED IN HORTICULTURE AND MEASURES TO PREVENT IT (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses the impact of aggressive environments on the service life and efficiency of horticultural machinery. Soil moisture, fertilizers, chemicals, and atmospheric factors accelerate corrosion processes in metal and polymer parts. In addition, the performance of the equipment decreases and maintenance costs increase. The article analyzes measures to prevent these negative effects by reducing corrosion and mechanical damage, using protective coatings, conducting regular preventive maintenance, and using modern materials.